2021
DOI: 10.1111/liv.14889
|View full text |Cite
|
Sign up to set email alerts
|

Sarco‐Model: A score to predict the dropout risk in the perspective of organ allocation in patients awaiting liver transplantation

Abstract: Background & Aims Sarcopenia in liver transplantation (LT) cirrhotic candidates has been connected with higher dropouts and graft losses after transplant. The study aims to create an ‘urgency’ model combining sarcopenia and Model for End‐stage Liver Disease Sodium (MELDNa) to predict the risk of dropout and identify an appropriate threshold of post‐LT futility. Methods A total of 1087 adult cirrhotic patients were listed for a first LT during January 2012 to December 2018. The study population was split into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…35 This suggest that patients with pathological BC profiles and low MELD might benefit from certain priorization of urgency for LT, eventually expediting LT using extended criteria allografts or living donors to prevent their waiting list dropout. 35 Besides further attempts reported recently by others to combine sarcopenia with MELD, 11,36 It should be noted that due to the current inmaturity of clinical diagnostic criteria in defining relevant pathologies of the SMC, the presence of significant sarcopenia, myosteatosis or sarcopenic obesity should not provide the sole basis to determine candidacy and urgency for LT. 16 Nevertheless, BC assessment provides an excellent platform which can be easily integrated into the clinical decision making as a supporting tool in the identification of patients presenting with an increased malnutritional risk who would benefit from an urgent and intensified pre-LT BC "upstaging approach" in terms of therapeutic interventions and "prehabilitation" programs. 16,35…”
Section: Clinical Scores Including Sarcopenia and Myosteatosismentioning
confidence: 99%
See 1 more Smart Citation
“…35 This suggest that patients with pathological BC profiles and low MELD might benefit from certain priorization of urgency for LT, eventually expediting LT using extended criteria allografts or living donors to prevent their waiting list dropout. 35 Besides further attempts reported recently by others to combine sarcopenia with MELD, 11,36 It should be noted that due to the current inmaturity of clinical diagnostic criteria in defining relevant pathologies of the SMC, the presence of significant sarcopenia, myosteatosis or sarcopenic obesity should not provide the sole basis to determine candidacy and urgency for LT. 16 Nevertheless, BC assessment provides an excellent platform which can be easily integrated into the clinical decision making as a supporting tool in the identification of patients presenting with an increased malnutritional risk who would benefit from an urgent and intensified pre-LT BC "upstaging approach" in terms of therapeutic interventions and "prehabilitation" programs. 16,35…”
Section: Clinical Scores Including Sarcopenia and Myosteatosismentioning
confidence: 99%
“…35 Besides further attempts reported recently by others to combine sarcopenia with MELD, 11,36 It should be noted that due to the current inmaturity of clinical diagnostic criteria in defining relevant pathologies of the SMC, the presence of significant sarcopenia, myosteatosis or sarcopenic obesity should not provide the sole basis to determine candidacy and urgency for LT. 16 Nevertheless, BC assessment provides an excellent platform which can be easily integrated into the clinical decision making as a supporting tool in the identification of patients presenting with an increased malnutritional risk who would benefit from an urgent and intensified pre-LT BC "upstaging approach" in terms of therapeutic interventions and "prehabilitation" programs. 16,35…”
Section: Clinical Scores Including Sarcopenia and Myosteatosismentioning
confidence: 99%
“…As an example, a recent study from Italy reported that an "urgency" model combining MELDNa and sarcopenia should be used to prioritize the sarcopenic patients with an initial MELDNa <20 on the list, further underlying the relevance of the nutritional status in the LT candidates and the scarce ability of the MELD system in capturing the actual complexity of these patients (38).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the initial sarcopenic status should consent to select a sub-group of HCC patients receiving TARE as downstaging for liver transplant. Therefore, the sarcopenic status should be of great importance with the intent to “shift” these patients to a potentially curative therapy, consenting to select patients with predictable positive outcomes after transplantation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%